A luminescent cationic MOF for bimodal recognition of chromium and arsenic based oxo-anions in water. Issue 29 (30th June 2021) - Dutta, Subhajit; Let, Sumanta; Shirolkar, Mandar M.; Desai, Aamod V.; Samanta, Partha; Fajal, Sahel; More, Yogeshwar D.; Ghosh, Sujit K.
Abstract : Selective bimodal "turn off/on" response in a water stable cationic MOF toward toxic water pollutants (CrO4 2−, Cr2 O7 2−, HAsO4 2−, and HAsO3 2− ). Abstract : Water pollution from heavy metals and their toxic oxo-anionic derivatives such as CrO4 2−, Cr2 O7 2−, HAsO4 2−, and HAsO3 2− has become one of the most critical environmental issues. To address this, herein, we report a new hydrolytically stable luminescent Zn(ii ) based cationic metal organic framework (MOF), iMOF-4C, which further successfully exhibited a rare dual "turn off/on" fluorescence response toward Cr(vi ), As(v ) and As(iii ) based oxo-anions respectively in water medium. In addition, iMOF-4C was found to maintain its superior selectivity in the presence of other concurrent anions ( e.g. SO4 2−, Cl −, Br −, ClO4 −, NO3 −, SCN − and CO3 2− ). More importantly, iMOF-4C exhibited an excellent selective and sensitive luminescence "turn-off" response towards CrO4 2− and Cr2 O7 2− anions in water medium with the quenching constant ( K sv ) values as high as 1.31 × 10 5 M −1 (CrO4 2− ) and 4.85 × 10 5 M −1 (Cr2 O7 2− ), which are found to be the highest among the values reported in the regime of MOFs. Interestingly, iMOF-4C showed fluorescence "turn-on" response toward HAsO4 2− and HAsO3 2− with an enhancement coefficient ( K ec ) of 1.98 × 10 4 M −1 and 3.56 × 10 3 M −1 respectively. The high sensitivity and low detection limits make iMOF-4C more feasible for real-time sensing of such toxic oxo-anions in an aqueous medium. Furthermore, the probable sensing mechanism has been investigated by DFT calculation studies and discussed in detail.